Long Noncoding RNAs in the Metastasis of Oral Squamous Cell Carcinoma - Xu, Yuming; Jiang, Erhui; Shao, Zhe; Shang, Zhengjun (Frontiers in Oncology, 2021)
Oral squamous cell carcinoma (OSCC) is a common malignant tumor worldwide. Metastasis is the main cause of the death of OSCC patients. Long noncoding RNAs (lncRNAs), one of the key factors affecting OSCC metastasis, are a subtype of RNA with a length of more than 200 nucleotides that has little or no coding potential. In recent years, the important role played by lncRNAs in biological processes, such as chromatin modification, transcription regulation, RNA stability regulation, and mRNA translation, has been gradually revealed. More and more studies have shown that lncRNAs can regulate the metastasis of various tumors including OSCC at epigenetic, transcriptional, and post-transcriptional levels. In this review, we mainly discussed the role and possible mechanisms of lncRNAs in OSCC metastasis. Most lncRNAs act as oncogenes and only a few lncRNAs have been shown to inhibit OSCC metastasis. Besides, we briefly introduced the research status of cancer-associated fibroblasts-related lncRNAs in OSCC metastasis. Finally, we discussed the research prospects of lncRNAs-mediated crosstalk between OSCC cells and the tumor microenvironment in OSCC metastasis, especially the potential research value of exosomes and lymphangiogenesis. In general, lncRNAs are expected to be used for screening, treatment, and prognosis monitoring of OSCC metastasis, but more work is still required to better understand the biological function of lncRNAs.